Theoretical modelling of oscillating water column wave energy converters - Deng, Zhengzhi (2014)
Offshore oscillating water column (OWC) wave energy converters, i.e., an OWC device with an arc-shaped supporting structure, an OWC device with a bottom-mounted V-shaped channel, an OWC device floating in heaving motion, and a heaving OWC device restrained by a linear spring-damper system (modelling another power take-off (PTO) system), are investigated theoretically, under the assumptions of linear water wave theory. A matched eigenfunction expansions method associated with a fast convergence technique is employed in cylindrical coordinate systems to study wave interactions with the four OWC converters in finite depth of water. Effects of supporting structures, OWC dimensions, wave direction on energy conversion efficiencies, and optimization of power take-off devices are discussed. The hydrodynamic performances, such as radiation susceptance, radiation conductance, added mass, and damping, are examined as well. Our results show that the present four OWC converters, compared with the truncated circular hollow OWC converter (studied by Evans & Porter (1997)), can significantly increase the conversion efficiency and widen the frequency range over which the conversion efficiency is high.